Epidemiology of Human Parvovirus 4 Infection in Sub-Saharan Africa - Colin P. Sharp; Marion Vermeulen; Yacouba K. Nébié; Cyrille F. Djoko; Matthew LeBreton; Ubald Tamoufe; Anne W. Rimoin; Patrick K. Kayembe; Jean K. Carr; Annabelle Servant-Delmas; Syria Laperche; G.L. Abby Harrison; et al. (Emerging Infectious Diseases, 2010)
Human parvovirus 4 infections are primarily associated with parenteral exposure in western countries. By ELISA, we demonstrate frequent seropositivity for antibody to parvovirus 4 viral protein 2 among adult populations throughout sub-Saharan Africa (Burkina Faso, 37%; Cameroon, 25%; Democratic Republic of the Congo, 35%; South Africa, 20%), which implies existence of alternative transmission routes.